Evaluation of the Biomechanical Properties of Endodontic Files with Different Taper Angles Using Finite Element Analysis - Mehmet Eskibağlar; Serkan Erdem (Firat University Journal of Experimental and Computational Engineering)

(untitled)
This study aims to evaluate the stress distribution of nickel-titanium (Ni-Ti) rotary tools with different conical angles during bending and torsion using finite element analysis (FEA). For the study, rotary file models with fixed taper angles of 0.02, 0.04, and 0.06 were modeled using Solidworks software. These models were transferred to Ansys software. It was performed according to the ISO 3630-1 specification using the SEA method to evaluate the flexibility and torsional stiffness of the files. According to the test results, the file system with a 0.02 taper angle showed higher flexibility when subjected to bending compared to the files with 0.04 and 0.06 taper angles. Regarding torsional resistance, the rotary file with a 0.06 taper angle demonstrated higher torsional resistance than the files with 0.02 and 0.04 taper angles. The geometry of the instrument affects the mechanical behavior (bending and torsional) of rotary files. Clinicians should be aware of the behavioral differences in rotary files and, in addition to following manufacturer instructions, should use the appropriate file according to the clinical situation